Semiconducting 2D-materials: Nano-sandbox for fundamental physics and new platform for optical coatings, light emission and quantum light sources - Knopf, Heiko; Lundt, Nils; Bucher, Tobias; Mupparapu, Rajeshkumar; Löchner, Franz; George, Antony; Neumann, Christof; Fasold, Stefan; Sedov, Evgeny; Waldherr, Max; Klaas, Martin; Tongay, Sefaating; et al. (Optics InfoBase Conference Papers, 2019)
Two-dimensional (2D) materials are interesting candidates for usage in optical coatings. The offer a natural access for the control of coating geometries down to the atomic scale. The set of 2D-materials, which is available for optical applications, spans dielectrics, semiconductors and (semi-)metals; but with sometimes vastly different properties from their bulk counterparts. In this talk I will present functionalized optical coatings consisting of 2D-materials but also functionalized optical coatings embedded with 2D-materials. I will discuss their specific properties, focusing on the development of excitonic systems and on highly nonlinear optical coatings for wavelength conversion and quantum light sources.
CRIS-Team Scopus Importer:2023-04-20